"Sex in Marriage Is a Divine Gift"? Evidence on the Quantity-Quality Trade-off from the Manila Contraceptive Ban. (17th December 2016) - Dumas, Christelle; Lefranc, Arnaud
Abstract: We analyze the trade-off between child quantity and child quality in developing countries by estimating the effect of family size on child's education in urban Philippines. To isolate exogenous changes in family size, we exploit a policy shock: in the late 1990s, the mayor of Manila enacted a municipal ban on modern contraceptives. Since other comparable cities in the Manila metropolitan area were not affected by the ban, this allows us to implement a difference-in-difference estimation of the effect on family size. We also exploit the fact that older mothers were less likely to become pregnant during the ban. Our results indicate that the contraceptive ban led to a significant increase in family size. They also provide evidence of a quality-quantity trade-off: increased family size led to a sizable decrease in educational attainment.